Balanta - Pintilie, Lucian (Romania : Parnasse Production ; Scarabee Films ; MK2 Productions S.A., 1992)
The first film by Lucian Pintilie after his return to Romania after 1989 portrays the country just before Ceausescu's downfall. It is the story of Nela, daughter of a former colonel of the Securitate, the Romanian political police. She refused to become an agent like her sister. After her father dies, she leaves the capital and accepts a job outside Bucharest. She is gang-raped en route to her working place. She also learns that her father was something less than a hero. She ends up in a small town, where she meets Mitica, a surgeon, and they both defend themselves against the harsh and absurd reality of later-Ceausescu era Romania by adopting a shield of cynicism. The movie presents an absurd world that cannot be made sense of; one in which any human being would lose his/her identity or self-respect.
Keywords: Fiction films